Socio-economic and behavioural determinants of fruit and vegetable intake in Moroccan women. Issue 5 (28th August 2014) - Landais, Edwige; Bour, Abdellatif; Gartner, Agnès; McCullough, Fiona; Delpeuch, Francis; Holdsworth, Michelle
Abstract: Objective: To estimate daily fruit and vegetable intakes and to investigate socio-economic and behavioural differences in fruit and vegetable consumption among urban Moroccan women. Design: A cross-sectional survey. Fruit and vegetable intake was measured with a single 24 h recall. Settings: A representative population-based survey conducted in the area of Rabat-Salé. Subjects: Women ( n 894) of child-bearing age (20–49 years). Results: Mean fruit and vegetable intake was 331 g/d (155 g/d for fruit and 176 g/d for vegetables). Only one-third (32·1 %) of women consumed ≥400 g/d and half the sample (50·6 %) were considered as low consumers, i.e. <280 g/d. Women of higher economic status ate significantly more fruit ( P <0·05) and more fruit and vegetables combined ( P <0·05). Women ate significantly less vegetables if they ate out of home more often or skipped at least one main meal (breakfast, lunch or dinner) or ate more processed foods ( P <0·05, P <0·01 and P <0·001, respectively). Fruit and vegetable diversity was not associated with any of the factors investigated. Conclusions: In this population, fruit and vegetable intakes are driven by different determinants. Indeed, while vegetable consumption was related only to behavioural determinants, fruit consumption was influenced only by economic status. Therefore, programmes promoting fruit and vegetable intake would be more effective if they account for these specific determinants in their design.